The impact of the COVID-19 restrictions on nursing home residents: An occupational perspective. Issue 3 (3rd July 2022) - Richardson, Grace; Cleary, Róisín; Usher, Ruth
ABSTRACT: Background : In Ireland, stringent restrictions were implemented to protect nursing home residents from contracting COVID-19. There is limited empirical research on how restrictions impacted residents' occupational engagement or well-being. This study explored the impact of COVID-19 restrictions on the occupational engagement of nursing home residents and considered implications for occupational science. Methods: Using qualitative descriptive design, semi-structured telephone interviews were conducted with five residents in one nursing home. Two online focus groups were conducted with seven nursing home staff working across five sites. Data were analysed using interpretive thematic analysis. Results : Three overarching themes emerged regarding residents' occupational engagement. 'Loss of valued occupation' related to residents' reduced engagement in social and leisure occupations, with an erosion of the quality and meaning of their routine daily activities. 'Counting the costs of restrictions on residents' well-being' revealed profound impacts on residents' physical and mental health, including reduced mobility, weight loss, reduced independence, low mood and increased fear, anxiety, and frustration. 'Finding resilience in the face of adversity' indicated some hopeful adaptive and coping strategies among residents. Conclusions and implications : This study brings an occupational perspective to the impact of COVID-19 on nursing home residents by highlighting issues beyond infection control and virus transmission. Findings contribute to occupational science knowledge by highlighting issues of occupational deprivation, occupational disruption and reduced occupational choice, and ripple effects on well-being. Nursing home residents' perspectives must be prioritised in future research and policy decision-making in responding and adapting to pandemics.